Rare Yeasts in Latin America: Uncommon Yet Meaningful (2023)
Systemic infections caused by rare yeasts are increasing given the rise in immunocompromised or seriously ill patients. Even though globally, the clinical significance of these emerging opportunistic yeasts is increasingly being recognized, less is known about the epidemiology of rare yeasts in Latin America. This review collects, analyzes, and contributes demographic and clinical data from 495 cases of infection caused by rare yeasts in the region. Among all cases, 32 species of rare yeasts, distributed in 12 genera, have been reported in 8 Latin American countries, with Trichosporon asahii (49.5%), Rhodotorula mucilaginosa (11.1%), and Saccharomyces cerevisiae (7.8%) the most common species found. Patients were mostly male (58.3%), from neonates to 84 years of age. Statistically, surgery and antibiotic use were associated with higher rates of Trichosporon infections, while central venous catheter, leukemia, and cancer were associated with higher rates of Rhodotorula infections. From all cases, fungemia was the predominant diagnosis (50.3%). Patients were mostly treated with amphotericin B (58.7%). Crude mortality was 40.8%, with a higher risk of death from fungemia and T. asahii infections. Culture was the main diagnostic methodology. Antifungal resistance to one or more drugs was reported in various species of rare yeasts.